La critique littéraire de Rachilde : du texte comme prétexte - Staroń, Anita (2023)
For over twenty-five years, Rachilde regularly commented on approximately thirty novels a month, in the column she signed for the “Mercure de France”. Sometimes her readings concluded in opinions on novelistic aesthetics, sometimes she spoke out on social issues or other prevailing matters. Thus, the texts she read became pretexts for presenting opinions sometimes far from literary subjects. Considering Rachilde’s sulfurous reputation, it seems interesting to examine her point of view on morality. The article focuses on some specific points contained in this notion: the relationship between the sexes, marriage and divorce, prostitution, offspring.
Keywords: literary criticism; morality; “Mercure de France”; novel; French literature